Studying Spatial Protein Quality Control, Proteopathies, and Aging Using Different Model Misfolding Proteins in S. cerevisiae - Schneider, Kara L.; Nyström, Thomas; Widlund, Per O. (Frontiers in Molecular Neuroscience, 2018)
Protein quality control is critical to maintain a functioning proteome. Misfolded or toxic proteins are either refolded or degraded by a system of temporal quality control and can also be sequestered into aggregates or inclusions by a system of spatial quality control. Breakdown of this concerted protein quality control network with age leads to an increased risk for the onset of disease, particularly neurological disease. Saccharomyces cerevisiae has been used extensively to elucidate protein quality control pathways and general evolutionary conservation of the protein quality control machinery has led to the development of several useful S. cerevisiae models of human neurological diseases. Key to both of these types of studies has been the development of several different model misfolding proteins, which are used to challenge and monitor the protein quality control machinery. In this review, we summarize and compare the model misfolding proteins that have been used to specifically study spatial protein quality control in S. cerevisiae, as well as the misfolding proteins that have been shown to be subject to spatial quality control in S. cerevisiae models of human neurological diseases.